Community leadership and the construction of political legitimacy Unpacking Bourdieu’s political capital in post-apartheid Johannesburg - Benit-Gbaffou, Claire; Katsaura, Obvious (My University, 2014)
In our attempt to unravel the structures, constraints and opportunities under which community leaders operate, we have been inspired, as many before us in different ways , by Bourdieu’s work on political capital, political representation and his analyses of the specificities of the ‘political field’ (Bourdieu, 1991). However, we also feel that his theoretical frames are built on reflections developed at a supra-local scale, in contexts of highly institutionalized or institutionalizing politics (national party apparatuses), and where the politics of informality are not at the center of his observations. We believe our perspectives on the micro-politics of the local in urban societies dominated by informality, and in globalizing and neoliberalizing governance contexts which see the proliferation of governance institutions (private and public, formal and informal, local, national and international) might bring new insights into the understanding of the complex construction of political legitimacies. In particular, we argue that community leaders – being both grounded locally, in close proximity to their constituencies; and in search of institutional recognition (by a party, or a fraction of the state) that might give them less uncertain legitimacy as well as possible access to material resources, need to build their political legitimacies not either from the bottom or from the top, but from both simultaneously. Following Bourdieu’s notion of double dealings (the need for what he calls ’professional politicians’ to fight in the political field as well as in the social field; for their own political positions and as representatives of their mandators), we then elaborate on instances where the relationships between the two legitimation processes (what we call here legitimation from the ‘bottom’ and from the ‘top’) reinforce one another or contradict one another
Our paper is divided into three sections. First, it was necessary to contextualize further our study in the various scholarly fields that have touched on issues of leadership and local politics. A second part is a presentation of, and elaboration upon, the concepts within Bourdieu’s work that we found useful to our theorization of community leadership. A third section is illustrating the relevance of this theoretical framework to unpack a complex South African story of local politics. The conclusion debates the relevance of this framework beyond the South African case.
Keywords: Community participation in urban governance; political domination processes; participatory governance settings; micro-political dynamics